Investigation of the Effects of Different Hydrophilic and Hydrophobic Comonomers on the Volume Phase Transition Temperatures and Thermal Properties of N-Isopropylacrylamide-Based Hydrogels - Ahmet Okudan; Abdullah Altay (International Journal of Polymer Science)
In this work, a series of thermally responsive terpolymers of N-isopropylacrylamide (NIPA) with three different comonomer contents was synthesized, and their swelling behaviour was studied as a function of composition and temperature. Temperature-sensitive, random cross-linked terpolymers of NIPA were prepared from methyl methacrylate (MMA), N-tert-butylacrylamide (NTBA), and acrylic acid (AA) using a free radical polymerization method. In the synthesis of terpolymer hydrogels, N,N-methylene bisacrylamide (BIS) was used as cross-linkers and ammonium persulfate (APS) as initiator. The NIPA content of the monomer feed varied from 80 to 50 mol %, and other comonomer feed varied from 40 to 5 mol %. The swelling equilibrium of these hydrogels was studied as a function of temperature and hydrophobic and hydrophilic comonomer contents. The swelling properties of the polymers were investigated in pure water at temperatures from 10 to 80°C. All of the synthesized gels were found to be sensitive to temperature. Glass transition temperature analyses and thermal analyses of the synthesized hydrogels were studied. The volume phase transition temperature and the swelling equilibrium (r) values of NIPA-based hydrogels synthesized in different feed ratios and in varying monomer contents were found in the range of 17–52°C and 14–51 g H2O/g polymer, respectively. The glass temperature (Tg) of the NIPA/AA/(MMA or NTBA) hydrogels synthesized with feed ratios of 50/40/10 was found to be 133 or 142°C, respectively. The initial and the end degradation that were determined for hydrogels at high temperatures indicated the quite good thermal stability of hydrogels. When the mass loss of the synthesized hydrogels was 50%, the temperatures were measured between 247 and 258°C.